Corporate Governance Country Assessment : Brazil - World Bank (Washington, DC, 2013)
This report assesses Brazil's corporate governance policy framework. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Brazil. It is an update of the 2005 corporate governance Report on the Observance of Standards and Codes (ROSC). Brazil's experience over the past 10 years has shown the value of corporate governance reforms, both in Brazil and around the world. Good corporate governance enhances investor trust, helps to protects minority shareholders, and can encourage better decision making and improved relations with workers, creditors, and other stakeholders. It is an important prerequisite for attracting the patient capital needed for sustained long-term economic growth. This report is organized into four sections: section one is the commitment of the public and private sectors to reform; section two is shareholder rights; section three is disclosure and transparency; and section four is boards of directors.